A study of music performance self-efficacy amongst students participating in music festivals - Tan, Gwendolina Shirney Swee Neo (2021)
The purpose of this study is to look into the students music performance self-efficacy who performed in the music festivals in Malay Gamelan and Wind Orchestra categories. All the four sources of self-efficacy in Banduras social cognitive theory which are 1) mastery experiences; 2) vicarious experiences; 3) verbal or social persuasion; and 4) physiological state were investigated. A survey method using Music Performance Self- Efficacy Scale (MPSES) by Zelenak (2011) was used. The data collected were then administered using descriptive analysis of mean to identify the highest to the lowest on the sources of self-efficacy. 150 Malaysian secondary school music students aged 14- 17 participated and completed the 30-item questionnaire online. The results shown that among the four sources of self-efficacy; mastery experiences had the highest mean (M = 4.23 on a 5-point scale). Whilst, the physiological state had the least mean (M = 3.85). The findings indicated that mastery experiences had the biggest impacts on students self-efficacy. The results of this study will provide music teachers and students with an understanding of maintaining and improving students self-efficacy in music performance. The study implicates that both the teachers and students can identify and focus more on sources of self-efficacy that the students lack off to help them increase their level of self-efficacy.